Analiza psihopatološkog stanja pojedinca i grupe i njihov utjecaj na širu društvenu zajednicu u patokratskom političkom sistemu / Analysis of the Psychopsthological State of the Union and the Group and their Effect on the Social Community in the Patocrative Political System - Kovačević, Sanela (Pregled: časopis za društvena pitanja / Periodical for social issues, 2018)
Review of a book Political Ponerology – A science on the nature of evil adjusted for political purposes by Andrew M. Lobaczewski, Red Pill Press, United State of America, 2006, 248 pp.